PENGARUH POLA ASUH ORANGTUA TERHADAP PRESTASI BELAJAR FIKIH SISWA KELAS VIII MADRASAH TSANAWIYAH NEGERI 1KOLAKA - rahman, kamiliah; Idris, Munadi; Akmir, Akmir (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
We can get education anywhere, both at school, within the family, and in the community. However, the most basic education is education that is obtained in the family environment, because family is the first education experienced by children. There are three types of parenting styles, namely authoritarian, democratic, and permissive parenting. Every family has different parenting styles in educating a child. The parenting pattern must be in accordance with the child's needs so that the child can develop properly and optimally, so that the achievement in the learning process that will be experienced by the child will run more optimally. In other words, the family's parenting pattern can affect children's learning achievement. The formulation of the problem in this study is whether there is an effect of parenting style on the students' fiqh learning achievement of class VIII Madrasah TsanawiyahNegeri 1 Kolaka? The research objective was to determine whether there was an effect of parenting style on the students' fiqh learning achievement of class VIII Madrasah TsanawiyahNegeri 1 Kolaka. This research is a correlational quantitative research. The independent variables in this study are parenting styles (authoritarian parenting = X1, permissive parenting = X2, and democratic parenting = X3), and fiqh learning achievement as the dependent variable. Sampling in this study using the Simple Random Sampling technique. From this study, it can be concluded that the results of the calculation of the T test for each variable X indicate that the significance value for the effect of authoritarian parenting (X1) on fiqh learning achievement (Y) is 0.001 <0.05 and the t-count value is -3.464> t table 1.972. . The significance value for the effect of permissive parenting (X2) on fiqh learning achievement (Y) is 0.003 <0.05 and the tcount -3.041>ttable 1.972. The significance value for the effect of democratic parenting (X3) on fiqh learning achievement (Y) is 0.000 <0.05 and the tcount value is 4.663> t table 1.972. Furthermore, the results of the F test found that the significance value for the effect of the variable X on Y is equal to 0.000 <0.05 and the value of Fcount 17.588>Ftable 2.65. From the results of the two tests above, it is said that there is an effect of parenting styles on the students' fiqh learning achievement of class VIII Madrasah TsanawiyahNegeri 1 Kolaka. The contribution of parenting parents to student achievement in learning was 21%.